Application of the defect distribution index to functional lung MRI of pediatric cystic fibrosis lung disease and controls - Kieninger, Elisabeth; Munidasa, Samal; Curdy, Marion; Streibel, Carmen; Zanette, Brandon; Woods, Jason; Latzin, Philipp; Ratjen, Felix; Santyr, Giles (Journal of cystic fibrosis, 2025)
Introduction - Functional magnetic resonance imaging (MRI) of the lung usually assesses lung impairment as ventilation defect percentage (VDP). However, VDP only reflects the overall burden of disease and does not characterize the regional distribution (i.e. pattern) of defects. The defect distribution index (DDI) is a metric which shows quantitatively how clustered versus scattered defects are with a higher DDI indicating more clustered defects. - Aim - To assess the applicability and validity of the DDI to 129Xe-MRI and PREFUL-MRI of CF lung disease. - Methods - The DDI algorithm was applied to fractional ventilation maps previously acquired with 129Xe-MRI and PREFUL-MRI of 37 children with CF and 13 healthy controls. - Results - The calculation of DDI was feasible for all MRI data. DDI was significantly higher in patients with CF compared to healthy controls (mean difference [95 % CI] 129Xe-MRI DDI60 %mean -1.94 [-2.86 - -1.02], p=0.0001), strongly correlated with other functional outcomes such as VDP and the lung clearance index, and decreased significantly in CF patients with pulmonary exacerbations after antibiotic treatment (e.g. 129Xe-MRI DDI60 % mean -1.03 [-0.44 - -1.63], p=0.002). - Conclusion - The DDI is applicable to functional 129Xe-MRI and PREFUL-MRI data providing complementary information to VDP by assessing defect distribution rather than defect size. It shows meaningful clinimetric properties and improves with treatment. The DDI shows potential as a parameter for comprehensive monitoring of CF lung disease and treatment.